Improving Post-Laparotomy Wound Healing With Snakehead Fish Extract - Husna, Innani Wildania; Siti Patonah; Dwi Agung Susanti; Selly Fitrilia (Jurnal EduHealth, 2024)
Post-laparotomy wound healing is a critical aspect of surgical recovery, often influenced by various factors including age and nutritional interventions. This study investigates the potential of snakehead fish extract in expediting wound healing processes among post-laparotomy patients. A total of 30 participants were enrolled, with 15 individuals assigned to both control and experimental groups. Participants were from the Jatirogo Community Health Center's working area. The distribution of respondents was analyzed based on age demographics and grouped by control and experimental categories. Wound healing progress following laparotomy surgery was monitored after the administration of snakehead fish extract. The majority of control group respondents were aged between 41 and 45 years (13.34%), while the experimental group comprised individuals predominantly aged 21-25 years and 41-45 years (13.34%). Analysis revealed significant differences in wound healing progress between the control and experimental groups, particularly after the administration of snakehead fish extract. Administering snakehead fish extract demonstrated a significant effect on post-laparotomy wound healing, particularly among participants in the experimental group. This suggests the potential therapeutic benefits of snakehead fish extract in surgical wound management, warranting further investigation and clinical application.